Exploring interactions between women who have experienced pregnancy loss and obstetric nursing staff: a descriptive qualitative study in China - Jialu Qian; Weihong Wang; Shiwen Sun; Mengwei Wu; Lu Liu; Yaping Sun; Xiaoyan Yu (BMC, 2022)
Abstract Background Contradictory interactions between bereaved women who have experienced pregnancy loss and obstetric nursing staff are becoming increasingly prominent. The aim of the present study was to gain an understanding of how women who have experienced pregnancy loss and obstetric nursing staff perceive their interactions, what influencing factors impacted their experiences. Methods A qualitative, exploratory study was conducted in a delivery room and six maternity wards of a tertiary hospital. Semi-structured interviews were performed with six nurses, 13 midwives and seven women who experienced pregnancy loss to collect rich information about how they make sense of their interactions. Thematic analysis was adopted to analyse the data. Results Five overarching themes were identified: (1) interaction characteristics, (2) interactive contradiction, (3) influencing factors of the interaction, (4) training needs and (5) suggestions for benign interactions. Conclusions Healthcare providers should be instructed in adopting a respectful and sympathetic attitude in communication, strengthening information support and offering patient-centred care for benign interactions. Ignoring women's needs and using disrespectful words should be avoided. Training for preparing nurses and midwives in perinatal bereavement care and addressing heavy emotional burden is necessary. Additional efforts are needed to improve medical services and to facilitate benign interactions in induced abortion care.